Cooperation and Coordination in Socially Monogamous Birds: Moving Away From a Focus on Sexual Conflict - Griffith, Simon C. (Frontiers in Ecology and Evolution, 2019)
Socially monogamous birds have provided a major focus of research in the field of sexual selection, providing insight into the evolution of ornaments, sexual dimorphism and sex roles. Following important theoretical work in the 1970’s, there has been a continued emphasis on elements of the sexual conflict between socially monogamous partners. The application of molecular tools enabled a significant research investment into the conflict over paternity. The differential allocation hypothesis, has been another well-worked area, focusing attention on the conflict over investment with a current or future partner, and being at the forefront of high-profile work on maternal effects. Whilst the conflict between the sexes has been a fascinating area of evolutionary biology over the past four decades, the level of conflict is often overstated, and our understanding of social monogamy is biased by taking the perspective of conflict rather than cooperation. For example, differential allocation in socially monogamous birds can be explained from an entirely cooperative perspective, as can much behaviour that is currently associated with sperm competition and the conflict over paternity. With over 80% of avian species forming socially monogamous bonds that are often life-long and can last for many decades, we need to redress the balance, and focus more attention on the benefits that both males and females gain from establishing, and maintaining socially monogamous partnerships. I highlight behavioural and morphological adaptations that feature strongly in socially monogamous birds, and that are deserving of more attention from the perspective of the high level of inter-individual cooperation and coordination that undoubtedly exists in many species. Whilst the focus of research has begun to shift recently, it will take many years to redress the bias towards sexual conflict that have taken the major share of empirical attention to this point.